Eco-driven choices: Green marketing orientation intervention toward green purchase intention in the home appliances industry - Abdur Rehman; Sheikh Raheel Manzoor; Atif Ullah; Heesup Han; Antonio Ariza-Montes; Miseldra Gil-Marín (Acta Psychologica, 2025)
Pakistan's growing environmental challenges and the emergence of a green market underscore the necessity of understanding how green marketing strategies shape consumer behavior. Accordingly, this study offers a comprehensive contextual analysis by examining the top home appliance sector, providing valuable insights into sustainable consumption within an emerging economy. The focus of the study is to measure the mediating effect of green brand image, green customer satisfaction, and green customer loyalty in between green marketing orientation and purchase intention. In addition, the moderating effect of brand social responsibility and green trust was also measured in these relationships. The survey method was used for data collection. The data was collected from the managerial cadre employees of the top five home appliance companies of Pakistan. The stratified random sampling technique was used. The collected data was initially analyzed via partial least square structural equation model (PLS-SEM) method. The findings revealed that green marketing orientation is a significant predictor of green brand image, green customer loyalty, green customer satisfaction, and green purchase intention. The findings further revealed that green brand image, green customer loyalty, and green customer satisfaction significantly mediate between the green marketing orientation and green purchase intention. Moreover, brand social responsibility and green trust were also found a significant moderator in between green customer loyalty, green brand image, green customer satisfaction, and purchase intention. This study contributes to the literature and covers the deficiencies in the past literature and the methodological dimensions related to green marketing orientation and purchase intention.